THE ARMED FORCES OF THE REPUBLIC OF POLAND AS AN EMPLOYER IN MODERN LABOUR MARKET IN OPINION OF SOLDIERS AND MILITARY STAFF - Marzena Piotrowska-Trybull (Acta Scientiarum Polonorum. Oeconomia, 2018)
As an employer, the Armed Forces of the Republic of Poland (AF RP) engage in modern market competition to win over the professional service recruits and military staff. Search and retention of properly trained personnel may help the Polish armed forces to carry out their tasks in efficiency way. The article shows the selected results of the pilot survey dealing with the image of the armed forces as perceived by the soldiers and the military employees. The survey has been carried out as an opinion poll to identify the attributes of the AF RP as an employer and to determine significance of these attributes for the soldiers and the military employees. Results of the survey indicate that the attributes that make the Polish army stand out as an employer at the labour market include: stable employment, professional development opportunities, teamwork orientation, challenges and high demands from the organisation members, relatively high remuneration, and sense of mission in striving to be useful to the society.